Elder - McIntyre, Daniel Mark (2018)
An essay and travelogue of a quest to uncover the legacy of the Vikings and how their influence affected the Celts and other civilizations on their path throughout history, Elder looks at one view of a group of people and considers the multiplicity of identity stripped from it. On the journey, the film follows the Vikings presence throughout Norway, Denmark, Sweden, and Iceland, extracting it from each site to be coupled with less dominant cultural memory. A personal diary dissecting history and heirlooms, Elder considers history carved as a monument, vulnerable to the erosions of time and truth.